The indirect effect of contextual factors on the emotional distress of infertile couples - Ramos, M. Moura (2012)
Few studies were dedicated to study the role of contextual factors, such as the socioeconomic status and urban rural residence in emotional distress of infertile couples. This study aimed to explore the impact of contextual factors on emotional distress, either directly or by affecting the importance of parenthood in one’s life which in turn affects emotional distress. In this cross-sectional study, 70 couples recruited during hormonal stimulation phase prior to IVF completed clinical and sociodemographic forms and self-report questionnaires assessing representations about the importance of parenthood and emotional distress. Path analysis using structural equation modelling was used to examine direct and indirect effects among variables. Results indicated that social economic status and Urban-Rural residence had an impact in emotional distress by affecting the representations about the importance of parenthood in one’s life. Gender differences were found regarding model paths, suggesting that the social context may contribute more to women’s emotional distress than to their partners’ distress. When delineating psychological interventions, health care providers should consider that cultural values about children and parenthood contribute to shape the infertility experience